ANALISIS KOMPARATIF PENDAPATAN USAHATANI PADI SAWAH YANG MENGGUNAKAN PUPUK BERIMBANG DAN TIDAK BERIMBANG DI DESA BALUASE KABUPATEN SIGI - Anwar Taher, Arifuddin Lamusa, Edi (AGROTEKBIS, 2016)
This study aims to determine the total costs, production volume, sales price and the amount of paddy farm income in the village Baluase South Dolo Sigi districts. The research was conducted in January to February 2015. The Respondent is done by simple random sampling method (Simple Random Sampling), considering that the number of respondents who were taken in the study were 20 farmers. The analysis used in this study is an analysis of income. The results showed that the average/ha income received by farmers for rice farming where the use of balanced fertilizerÂ  average income of Rp 20.91405 million/ha, while the average income does not use a balanced fertilizer Rp 8.2358 million/ha. By means paddy rice farming which uses balanced fertilizer gave the comparison of real incomes compare to the one not using balanced fertilizer.